The Value of Emotion: How Does Episodic Prospection Modulate Delay Discounting? - Liu, Lei (Public Library of Science, 2013)
BACKGROUND: Humans often show impatience when making intertemporal choice for monetary rewards, preferring small rewards delivered immediately to larger rewards delivered after a delay, which reflects a fundamental psychological principle: delay discounting. However, we propose that episodic prospection humans can vividly envisage exerts a strong and broad influence on individuals' delay discounting. Specifically, episodic prospection may affect individuals' intertemporal choice by the negative or positive emotion of prospection. METHODOLOGY/PRINCIPAL FINDINGS: The present study explored how episodic prospection modulated delay discounting by emotion. Study 1 showed that participants were more inclined to choose the delayed but larger rewards when they imaged positive future events than when they did not image events; Study 2 showed that participants were more inclined to choose the immediate but smaller rewards when they imaged negative future events than when they did not image events; In contrast, study 3 showed that choice preferences of participants when they imaged neutral future events were the same as when they did not image events. CONCLUSIONS/SIGNIFICANCE: By manipulating the emotion valence of episodic prospection, our findings suggested that positive emotion made individuals tend to choose delayed rewards, while negative emotion made individuals tend to choose immediate rewards. Only imaging events with neutral emotion did not affect individuals' choice preference. Thus, the valence of imaged future events' emotion might play an important role in individuals' intertemporal choice. It is possible that the valence of emotion may affect the changed direction (promote or inhibit) of individuals' delay discounting, while the ability to image future events affects the changed degree of individuals' delay discounting.